Multilayer plug assisted thermoforming : concept and practical usefulness - Duarte, F. M. (2006)
This work presents a methodology to improve the final thickness distribution of thermoformed parts. The conventional plug is replaced by a new version containing concentric layers with independent displacements. The results show that thickness gradients can be significantly reduced, with a simultaneous increase of the minimum values. Varying the relative displacement of the inner layers can bring about significant differences in the final thickness distribution, thus enabling the production of parts with prescribed thickness profiles that maximise their mechanical performance.